2006
DOI: 10.1021/jo0524270
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Conformations of Benzenesulfonamide:  Gas Electron Diffraction and Quantum Chemical Calculations

Abstract: The molecular structure and conformational properties of benzenesulfonamide, C6H5SO2NH2, were studied by gas electron diffraction (GED) and quantum chemical methods (MP2 and B3LYP with different basis sets). The calculations predict the presence of two stable conformers with the NH2 group eclipsing or staggering the SO2 group. The eclipsed form is predicted to be favored by about 0.5 kcal/mol. According to GED, the saturated vapor over solid benzenesulfonamide at a temperature of 150(5) degrees C consists of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
(26 reference statements)
3
25
0
Order By: Relevance
“…It is well known that their biological properties correlate strongly with the structure and conformational properties of the respective compounds. Recently, a study has been reported on the geometric structure and conformation of benzene sulfonamide, C 6 H 5 SO 2 NH 2 , on the basis of combined study of gas electron diffraction (GED) and quantum chemical calculations [48]. According to this study, the saturated vapor over solid benzene sulfonamide at a temperature of 150(5) C consists predominantly of a conformer with the SAN bond perpendicular to the benzene ring and the NH 2 group eclipsing the SO 2 entity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that their biological properties correlate strongly with the structure and conformational properties of the respective compounds. Recently, a study has been reported on the geometric structure and conformation of benzene sulfonamide, C 6 H 5 SO 2 NH 2 , on the basis of combined study of gas electron diffraction (GED) and quantum chemical calculations [48]. According to this study, the saturated vapor over solid benzene sulfonamide at a temperature of 150(5) C consists predominantly of a conformer with the SAN bond perpendicular to the benzene ring and the NH 2 group eclipsing the SO 2 entity.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that piperazine derivatives show antiproliferative activity against many cancer cells [32][33][34]. In order to search for new compounds with antiproliferative activity against prostate cancer, all new synthesized compounds (4a-x) were evaluated for their in vitro antiproliferative activities against the human androgenindependent prostate cancer cell line C4-2, using BrdU incorporation assay.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…SKF is comprised of a tetrahydroisoquinoline ring substituted with a sulphonamide group at the 7-position. The conformational preferences of aromatic sulphonamide groups have been studied previously using gas phase electron diffraction and high-level QM calculations [30]. Benzene sulphonamide has two degenerate energy minima in which the S-N bond lies perpendicular to the aromatic ring with the dihedral angle being either 90°or -90°.…”
Section: Case 2: the Conformation Of A Sulphonamide Groupmentioning
confidence: 99%